(untitled) (Kawalu: Journal of Local Culture, 2024)
The Chinese community in Yogyakarta is used to culturally divided into two groups: peranakan and totok. The peranakan were Chinese with local roots. This group was usually influenced by local Javanese culture. Their language also often used Javanese language elements. Mosttotok were Chinese immigrants and their immediate descendants who were less acculturated and more strongly oriented towards China. They spoke various Chinese dialects at home rather than speaking Indonesian. This paperobserves these two Chinese communities in Yogyakarta, particularly with reference to the Gondoman district, one of the largest areas with Chinese ethnic population. I emphasize here that Gondomanan klenteng is an ambivalence worship place. Klenteng and Buddha Prabhavihara are two temples that having different rituals and different religious teachings. The Gondomanan klenteng has been obligating klenteng members to pray to the ancestor, whereas the same members have also practiced Buddhism in the Buddha Prabhavihara, in the backside of the klenteng. The two templesrepresent two religions; klenteng indicates traditional religion that is practiced by their ancestors, while vihara is a worship place that implements some Buddhism obligations. This fact indicates an ambivalent worship place.